Effects of Physical Exercise on Chemotherapy-Induced Peripheral Neuropathy: A Systematic Review and Meta-Analysis...2024 American Society for Pain Management Nursing (ASPMN) Annual Conference, October 16-19, 2024, San Antonio, TX. - Amarelo, Anabela; da Mota, Marisa Cristina Correia; Amarelo, Bruno Luís Pires; Ferreira, Marta Campos; Fernandes, Carla Sílvia (Pain Management Nursing, 2025)
The aim of this systematic review and meta-analysis is to systematically collect, evaluate, and critically synthesize research findings on the effects of physical exercise on chemotherapy-induced peripheral neuropathy (CIPN). The Joanna Briggs Institute (JBI) methodology for systematic reviews was adopted for this study. We searched the Medline®, CINAHL, SportDiscus, and Scopus databases to identify relevant articles published from inception to March 2024. This review was reported in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Twelve studies met the inclusion criteria, totaling 928 participants. Interventions ranged from aerobic and resistance exercises to balance and strength training. A range of physical exercise interventions was explored, including brisk walking, endurance training, weight exercises, and resistance bands, as well as combined programs of aerobics, resistance, and balance training, all tailored to improve symptoms and quality of life in patients with chemotherapy-induced peripheral neuropathy. The meta-analysis focused on five studies that used the FACT/GOG-Ntx scale indicated a standardized mean difference of 0.50 (95% CI: 0.26, 0.74), favoring exercise, reflecting significant improvements in neuropathy symptoms. The heterogeneity among the studies was low (I² = 2%), suggesting consistency in the beneficial effects of exercise. From the results analyzed, the descriptive analysis of the 12 included studies shows promising outcomes not only related to individuals' perceptions of CIPN severity but also in terms of physical functioning, balance, ADL (Activities of Daily Living) performance, pain, and quality of life. The findings support the integration of structured exercise programs into oncological treatment plans.